2021
DOI: 10.1155/2021/5539878
|View full text |Cite
|
Sign up to set email alerts
|

Ipomea batatas Leaf Powder from Cameroon: Antioxidant Activity and Antihyperlipidemic Effect in Rats Fed with a High-Fat Diet

Abstract: The present study consists of analyzing the phytochemical composition of Ipomoea batatas leaf powders and evaluating their antihyperlipidemic effect on rats receiving a high-fat diet. Ipomoea batatas leaves were collected from four agroecological areas of Cameroon, and powders were obtained after washing, drying, grinding, and sieving. Standard analytical methods were used to determine the phytochemical composition of two varieties (IRAD-tib1yellow-V1 and IRAD-1112white-V2) from North Z1, Adamawa Z2, West Z3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In addition to this, they also investigated the anthocyanin content and found proanthocyanidins content in the range from 175.27 g GAE/100 gDW to 176.04 mgCE/100 gDW. 5 Flavonoids act as an antioxidant with radical scavenger activity. The mechanisms of antioxidant action of flavonoids include suppressing reactive oxygen © 2023 the authors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this, they also investigated the anthocyanin content and found proanthocyanidins content in the range from 175.27 g GAE/100 gDW to 176.04 mgCE/100 gDW. 5 Flavonoids act as an antioxidant with radical scavenger activity. The mechanisms of antioxidant action of flavonoids include suppressing reactive oxygen © 2023 the authors.…”
Section: Resultsmentioning
confidence: 99%
“…The different parts of this plant have been studied since they are used in folk medicine for the treatment of several disorders including acne and anemia, due to its antiviral applications, and agency as a anthelminthic vermifuge or dewormer. 5 In addition to their antidiabetic and antiviral properties, I. batatas leaves have been used to treat infectious disorders in Brazil. 6 Several studies on the leaves of I. batatas collected from Malaysia and Brazil have found excellent antioxidant activity due to the presence of flavonoids, β-carotene, anthocyanins and phenols.…”
Section: Introductionmentioning
confidence: 99%
“…evaluated the effects of rich polyphenols star anis tea in HFD-sugar induced obesity rats, and they observed that the cholesterol levels were lower in the treatment groups . Furthermore, Mbouche Fanmoe et al in 2021 observed that Ipomea batatas Leaf powder reduced serum total cholesterol, LDL-cholesterol, and triglycerides in rats fed a high-fat diet, and this effect was attributed to the high content of polyphenols in the powder …”
Section: Resultsmentioning
confidence: 99%
“…18 Ipomoea batatas leaf powder showed good antiradical activity and effectively reduced total cholesterol, triglyceride, and LDL cholesterol levels. [19][20][21] Metformin is a glucose-lowering agent, and its primary mechanism is inhibition of hepatic gluconeogenesis through activation of adenosine monophosphate kinase (AMPK), which suppresses glucagon-stimulated glucose production and increases glucose uptake via glucose transporter type 4 (GLUT4) in muscle and liver cells. [22][23][24]…”
Section: Discussionmentioning
confidence: 99%